EFFECT OF DIFFERENT COATING MATERIAL ON THE STORAGE BEHAVIOR OF CUSTARD APPLE (ANNONA SQUAMOSA L.) - SWATI GOHLANI; B.P. BISEN (The Bioscan, 2012)
Custard apple, being a climacteric fruit, has short shelf-life because of fast ripening followed by senescence accompanied with quality changes and decay loss. The physiological weight loss of fruits, irrespective of treatments, increased with advancement of storage period but, the minimum (20.99%) physiological weight loss was recorded in the fruits treated with sago 5 per cent and maximum (39.11%) was observed under untreated fruits at 8 days of storage. The fruits treated with fine coating of sago (10%) retained excellent fruit quality with highest TSS (30ºBrix) and higher sugar (total and reducing sugar) (31.19 and 17.28) at 8 days of storage. The minimum sugar (total and reducing sugar) percentage i.e. 21.11 and 9.10 per centage, respectively and maximum vitamin ‘C’ content (47.10 mg/100g of pulp) was recorded in the fruits treated with Cacl2 (1.5%) whereas, control treated fruits recorded the least (23.10 mg/100g pulp) at 8 days of storage and marketable fruits were available even up to eight days of storage. Therefore, identification of natural products which produces desirable coating material with necessary amendment is the appropriate technology that can be explored for improving post-harvest storage and marketing efficiency.